Nonlinear Finite Element Modeling of Shear Behavior of Concrete Deep Beams Reinforced with Internal Glass Fiber-Reinforced Polymer Bars by ANSYS - Mohammed, Shuaaib Abdalla; Rafiq, Serwan Khurshid; Aziz, Zana Abdalla (Sulaimani Journal for Engineering Sciences, 2022)
The purpose of this paper is to numerically trace the behavior of concrete deep beams reinforced with internal Glass Fiber-Reinforced Polymer (GFRP) bars and containing no web reinforcement by using ANSYS program. For this purpose, a finite element model is used for concrete deep beams that previously examined in an experimental study and its predicted failure loads were compared with the actual failure loads. The results of the finite element model were in a good agreement with observations from the experimental study. The comparisons showed that the used model has the ability to capture the shear behavior, as well as load-deflection response and crack patterns of deep beams reinforced with internal GFRP bars in the entire range of loading. The paper is also covered a parametric study on shear span-to-depth (a/d) ratio, GFRP reinforcement ratio and concrete compressive strength which they usually have high impacts on the behavior of fiber-reinforced concrete beams. The results of the parametric study showed that the ultimate failure load of beams reinforced with GFRP bars was higher than that of steel-reinforced concrete beams. The maximum failure load was observed to decrease by decreasing the a/d ratio. The stiffness and ductility of the beams were increasing by increasing the reinforcement ratio.
Keywords: Deep beams; fiber-reinforced polymer bars; failure mechanisms; shear span-depth ratio (a/d)